Cerebrospinal fluid acetylcholinesterase in progressive supranuclear palsy: reduced activity relative to normal subjects and lack of inhibition by oral physostigmine. Issue 9 (September 1991) - Atack, J R; Litvan, I; Thal, L J; May, C; Rapoport, S I; Chase, T N
Abstract : Acetylcholinesterase (AChE) activity was measured in lumbar cerebrospinal fluid (CSF) of 11 patients with progressive supranuclear palsy (PSP) and 18 age-matched healthy control subjects. Mean CSF AChE activity in PSP subjects was significantly reduced by 31% relative to control subjects (p less than 0.002). In the light of evidence of a central cholinergic deficit, physostigmine was administered orally (0.5-2.0 mg every two hours, six times a day for 10 days) to eight of the 11 PSP patients. CSF was sampled when the patients were on placebo and when receiving physostigmine and CSF AChE and butyrylcholinesterase (BChE) activities were measured. There was no significant change in either CSF AChE or BChE activities following physostigmine treatment. These data suggest that the doses of physostigmine used were insufficient to produce marked inhibition of AChE within the central nervous system.